2017
DOI: 10.4236/ojn.2017.75040
|View full text |Cite
|
Sign up to set email alerts
|

Realities of Reflective Practice Skill among Public Health Nurses in Japan and Related Learning and Lifestyle Factors

Abstract: Background: According to the diversification of the health needs and the expansion of health disparities, it is necessary to raise their reflective practice skills so that PHNs present more appropriate activities. The purpose of this study was to elucidate the realities of reflective practice skills among public health nurses in Japan and identify related factors. Methods: This study covered 1725 public health nurses in the Chugoku/Shikoku area. We conducted an anonymous self-completed questionnaire survey. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Although the clinical practice settings described by participants varied, possibly due to the study’s use of Gibbs’s reflective cycle, the study found that reflection was seen as beneficial for participants' feelings, thoughts, and actions [ [18] , [19] , [20] ]. Participants felt it was meant to reflect on events in clinical practice to help them do things the next time they faced a similar situation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the clinical practice settings described by participants varied, possibly due to the study’s use of Gibbs’s reflective cycle, the study found that reflection was seen as beneficial for participants' feelings, thoughts, and actions [ [18] , [19] , [20] ]. Participants felt it was meant to reflect on events in clinical practice to help them do things the next time they faced a similar situation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Structured templates, however, may compromise the quality and authenticity of the data collected. Nevertheless, Gibbs' reflective cycle was found to be an effective, useful, and enjoyable method for teaching clinical education [ 18 , 19 ]. The Gibbs’s reflective cycle [ 19 ] also showed that most people’s knowledge and understanding are obtained from a reflection of the experience, and constantly thinking can lead to a better understanding of things, and the guidance of action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflective Practice is one way of improving practical capabilities [1], and is increasingly being introduced in professional and school education along with Reflective Journal (hereinafter "RJ") and Portfolio [2]. Existing studies and surveys of public health nurses in Japan have shown the absence of a correlation between Reflective Practice Skills and years of experience [3], pointing to the need to consider evaluation and improvement measures to promote Reflective Practice more effectively, so that the accumulation of experience may lead to qualitative improvement in those skills.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to create high-quality expertise, it is necessary to focus on the progress throughout the reflective cycle and the content of reflection. A Reflective Practice Skills scale (hereinafter "RPS") has been developed as an objective measure of the quality of such progress [3]. However, no relationship has been identified between RPS, which evaluates the quality of the reflective cycle, and the quality of reflection itself.…”
Section: Introductionmentioning
confidence: 99%